Clarifying the link between anxiety and conspiracy beliefs: A cross-sectional study on the role of coping with stressors. (February 2023) - Krüppel, Jonas; Yoon, Dahlnym; Mokros, Andreas
Abstract: Recent theoretical models view conspiracy beliefs as an individual reaction to threatening experiences, an assumption that is in line with empirical relationships between conspiracy beliefs and feelings of anxiety and distress. The purpose of this study was to examine whether these relationships can be explained by the frequent use of specific coping strategies. In two consecutive online studies ( N 1 = 589, N 2 = 177), anxiety, coping, and conspiracy beliefs were measured using questionnaires (Study 1 and Study 2) as well as a behavior-based measure (Study 2). Conspiracy beliefs were linked to higher levels of dispositional, but not situational anxiety. With respect to coping with stressors, conspiracy beliefs were positively correlated with vigilance and unrelated to avoidance. No moderator or mediator effects of the individual coping style on the relationship between conspiracy beliefs and anxiety were found. These results imply that individuals who endorse conspiracy theories are rather more anxious and less tolerant to ambiguity. Given the weak effect sizes and the focus of the extant models, however, replications should target the links between coping, anxiety and fear. Highlights: Conspiracy beliefs are related to elevated levels of trait, but not state anxiety. Conspiracy believers actively explore potential threats rather than avoiding them. Bivariate relationships are unaffected by coping style and self-efficacy. These results highlight the value of information campaigns.